Fellini the Sixties - Bowman, Manoah (Running Press, 2015)
"Fellini: The Sixties is a stunning photographic journey through the director's most iconic classics: La Dolce Vita, 81/2, Juliet of the Spirits, and Fellini Satyricon. Carefully selected imagery from the Independent Visions photographic archive, many published here for the first time, illuminate these films as they have never been seen before, and reveal fascinating details of the director's working style and ebullient personality. With more than 150 photographs struck from original negatives, these images spring to life from the page with the depth and quality of the films themselves. Complemented with insightful essays from contemporary writers, Fellini: The Sixties is a true testament to the man and his work, a remarkable compendium of the legendary filmmaker's greatest achievements"--Jacket
"Turner Classic Movies"--Cover
Keywords: Fellini, Federico / Criticism and interpretation; Fellini, Federico; Motion picture producers and directors / Italy; Nineteen sixties; Motion picture producers and directors; Italy; Italien